Brain rules : 12 principles for surviving and thriving at work, home, and school - Medina, John, 1956- (Pear Press, 2008)
In Brain Rules, Dr. John Medina, a molecular biologist, shares his lifelong interest in how the brain sciences might influence the way we teach our children and the way we work. In each chapter, he describes a brain rule--what scientists know for sure about how our brains work--and then offers transformative ideas for our daily lives.--From www.brainrulesbook.com .